The Relationship Between Diet Quality and Nutritional Status of Pregnant Women in Bandung Regency - Fatimah, Luthfiah Nurul (Tadulako University, 2025)
Diet quality in pregnant women is a crucial factor in supporting maternal health and optimal fetal development. A diverse and balanced diet helps fulfill the increased macronutrient needs during pregnancy. However, many pregnant women in Indonesia, including those in Cangkuang District, Bandung Regency, still fail to meet the recommended dietary diversity. This study aimed to analyze the relationship between diet quality and the nutritional status of pregnant women in Cangkuang District, Bandung Regency. This quantitative study used a cross-sectional design and involved 60 pregnant women selected by convenience sampling. Data were collected using subject characteristic questionnaires, 24-hour food recall forms, and food frequency questionnaires. Diet quality was assessed using the Minimum Dietary Diversity for Women (MDD-W) score. Univariate analysis was used to describe participant characteristics, and the Spearman correlation test was used to analyze the relationship between diet quality and nutritional status. The results showed a significant relationship between diet quality and nutritional status (p ≤ 0.05). A total of 63.3% of the pregnant women had an MDD-W score ≥5, indicating adequate dietary diversity. A diverse diet was significantly associated with better nutritional status among pregnant women. Focused interventions, such as nutrition education and food supplementation, are recommended to improve dietary diversity in this group. Keywords : Pregnant women; diet quality; nutritional status